Development of an expert system of herb plants as traditional medicine / Hafsah Othman - Othman, Hafsah (2003)
The new millennium offers a wide range of opportunities for the construction industry. The transition from information to knowledge era is beginning to take place in the new globalised world where IT is the enabling mechanism.